Trends in Policy on the Prevention and Control of Non-Communicable Diseases in Japan. Issue 4 (2nd October 2017) - Ezoe, Satoshi; Noda, Hiroyuki; Akahane, Naoki; Sato, Osamu; Hama, Takashi; Miyata, Tatsunori; Terahara, Tomohiro; Fujishita, Manami; Sakamoto, Haruka; Abe, Sarah Krull; Gilmour, Stuart; Shobayashi, Tokuaki
Abstract: Abstract— For the past decades Japan has remained number one in a range of population health metrics including the world's longest healthy life expectancy. While this was achieved through various socioeconomic factors besides public health interventions, health promotion policies to prevent and control non-communicable diseases (NCDs) played a major role. Japan introduced its first comprehensive national plan to prevent and control NCDs in 1978 and has revised the plan every decade since. These 10-year policy packages were instrumental in galvanizing stakeholders, while adapting to changing social, behavioral, and epidemiological trends. In this article, we provide an overview of trends in policy on the prevention and control of NCDs in Japan with a focus on successes and challenges especially due to a rapidly aging population. Through this review we aim to share the lessons learned in Japan for other countries tackling or expecting to be challenged by NCDs. These lessons include the role of multisectoral approaches, clear goals and targets with effective monitoring and evaluation mechanisms, addressing social aspects, adjustment to the local context, and foreseeing future demographic transition. Japan is committed to contributing to the world as a forerunner of the health challenges posed by unprecedented demographic change, by sharing its lessons in the global quest to create a world where all people can live longer and healthier lives.